The Role of the Pamong Praja Police Unit in Enforcing Regional Regulation Number 2 of 2020 concerning the Implementation of Peace, Public Order, and Community Protection - Almuzamil Falaq; Mashendra; L.M. Ricard Zeldi Putra; Waode Novita Ayu Muthmainna (AIQU: Journal Multidiscipliner of Science, 2024)
Indonesia, as the world's largest archipelagic country, possesses an extensive coastline of 99,093 kilometers, making it rich in marine biodiversity and fisheries potential. Coastal areas provide significant economic benefits, serving as both a livelihood source for local communities and a major attraction for marine tourism. However, these regions are increasingly threatened by environmental degradation due to rapid population growth, illegal settlements, excessive resource exploitation, and poor waste management. These issues necessitate strong regulatory frameworks to ensure sustainable coastal management. This study examines the enforcement of Buton Regency Regional Regulation No. 2 of 2020 concerning Orderly Coastal Areas, with a focus on the role of Satpol PP (Civil Service Police Unit) in maintaining public order and environmental conservation in Kambula-Bulana Village. Utilizing an empirical legal research approach, data was collected through field observations and interviews with key stakeholders. Findings indicate that regulatory enforcement remains suboptimal due to inadequate funding, low public awareness, and weak cross-sector coordination. Illegal construction and improper waste disposal persist as major challenges, emphasizing the need for stronger law enforcement, community engagement, and integrated policy implementation to achieve sustainable coastal governance.